2018
DOI: 10.1039/c7ob02965a
|View full text |Cite
|
Sign up to set email alerts
|

A fluorescent activatable probe for imaging intracellular Mg2+

Abstract: An BODIPY probe for detection and imaging of Mg2+ without interference from Ca2+ is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…The BC- series of compounds have different numbers and positions of methyl groups on the BC , while the BP- series of compounds are modified by changing positions of acetamido groups on the phenyl ring. As the intramolecular rotation of the BODIPY rotors was found closely related to viscosity sensitivity, BODIPY derivatives applied in this study contained the 1,7-substituted core to inhibit the free rotation. …”
Section: Resultsmentioning
confidence: 96%
“…The BC- series of compounds have different numbers and positions of methyl groups on the BC , while the BP- series of compounds are modified by changing positions of acetamido groups on the phenyl ring. As the intramolecular rotation of the BODIPY rotors was found closely related to viscosity sensitivity, BODIPY derivatives applied in this study contained the 1,7-substituted core to inhibit the free rotation. …”
Section: Resultsmentioning
confidence: 96%
“…Some APTRA-based probes developed in recent years also have higher affinity for Ca 2+ than Mg 2+ . Although intracellular Ca 2+ concentration ([Ca 2+ ] i ) is estimated to be around 100 nM, it can reach levels of about 10 μM by various stimulation, and hence, fluorescence signals from those probes are often influenced by Ca 2+ . Therefore, our group has developed the highly selective Mg 2+ fluorescent probe KMG series based on the β-diketone moiety. , In recent years, some other groups also developed highly selective Mg 2+ ligands without interference from Ca 2+ , which indicates that highly selective Mg 2+ probes are required for in detail investigation. However, the fluorescent dye moieties of these probes show green to red fluorescence emission, such as fluorescein (KMG-104: λ abs /λ em = 504/523), rhodamine (KMG-301: λ abs /λ em = 563/590), and styryl boron-dipyrromethene (MagQ-1: λ abs /λ em = 600/635) as summarized in Table .…”
mentioning
confidence: 99%
“…During the course of our studies, Vendrell and coworkers reported a related BODIPY compound, devoid of the water-solubilizing carboxypropyl groups, and demonstrated similar Mg 2+ sensing properties but only in aqueous/organic solvent mixtures. 33…”
Section: Resultsmentioning
confidence: 99%